Weight Gain Outcomes Following Surgical Management of Laryngomalacia in Pediatric Patients: A Systematic Review (Asian Journal of Pharmaceutics (AJP), 2025)
Laryngomalacia is the most common congenital upper airway disorder in infants, characterized by dynamicsupraglottic collapse, causing inspiratory stridor, feeding difficulties, and failure to thrive (FTT). While mildcases resolve spontaneously, severe cases often require surgical intervention. Supraglottoplasty, the gold-standard surgical treatment, alleviates airway obstruction, improves feeding efficiency, and promotes weightgain. However, outcome variability and methodological differences highlight the need for a systematic review.This review evaluates supraglottoplasty’s efficacy and safety in severe laryngomalacia, focusing on weightgain, feeding efficiency, respiratory improvement, and complications. Following Preferred Reporting Items forSystematic Reviews and Meta-Analyses guidelines, PubMed and Cochrane Library were systematically searchedfor studies on pediatric patients undergoing supraglottoplasty. Data on weight gain, feeding, respiratory outcomes,and complications were extracted, and quality was assessed using the Newcastle–Ottawa scale. Thirteen studies(706 patients) were included. Mean age at surgery ranged from 2 weeks to 15.6 months. Weight gain improvedsignificantly, with percentile increases of 15–26 points, particularly in infants 90%. Complication rates were low (